2012
DOI: 10.1902/jop.2011.110408
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Amelogenin on Mineralization of Cementoblasts and Periodontal Ligament Cells

Abstract: The present study shows that rh174 enhances mineralization accompanied by upregulation of mineralization markers in HCEMs, whereas it has no effect on that in HPDLs, suggesting different effects of amelogenin on PDL and cementum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…In the present study, as mineralized nodules are formed on stimulation with SP, this alizarin red technique is used to evaluate calcium deposition. The alizarin red technique has been used to demonstrate calcification of PDL cells induced by EMD 35‐37 . The results of the present study show that exposure to SP in osteogenic medium enhances both the number of mineralized nodules and extracellular calcium deposition in PDLSCs.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the present study, as mineralized nodules are formed on stimulation with SP, this alizarin red technique is used to evaluate calcium deposition. The alizarin red technique has been used to demonstrate calcification of PDL cells induced by EMD 35‐37 . The results of the present study show that exposure to SP in osteogenic medium enhances both the number of mineralized nodules and extracellular calcium deposition in PDLSCs.…”
Section: Discussionsupporting
confidence: 49%
“…Although EMD enhanced the proliferation and mineralization of PDL cells, EMD by itself did not promote their full differentiation into osteoblasts, as assessed by the expression of osteoblast‐specific markers 26 . Moreover, a recent report showed that full‐length amelogenin enhanced osteoblast differentiation markers in human cementoblasts but had no such effect on human PDL cells isolated from the first premolar 37 . On the other hand, TGF‐β has been suggested to regulate the osteoblast differentiation of PDL cells, as well as PDL cell proliferation 38 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous in vitro and in vivo studies have shown that EMD promotes the regeneration of periodontal tissues and affects the proliferation and mineralization of cells, such as cementoblasts and periodontal ligament cells [28-34]. EMD also promotes the regulation of osteoclastogenesis, the proliferation and migration of periodontal cells, and also stimulates the signal transduction of bone morphogenic protein and transforming growth factor-β [31,35-40].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies have demonstrated that an N‐terminal amelogenin peptide induces osteogenic differentiation of mesenchymal stem cells . It has been suggested that amelogenin exerts different effects on mineralization depending on the cell type . The differential activity of amelogenin may be attributable to phenotypic differences between various cell types.…”
Section: Discussionmentioning
confidence: 98%